The impact of the COVID-19 pandemic on infertility patients and endometriosis patients in the Netherlands. Issue 4 (October 2021) - Rosielle, Kimmy; Bergwerff, Jasmijn; Schreurs, Anneke M.F.; Knijnenburg, José; De Bie, Bianca; Maas, Jacques W.M.; Nap, Annemiek W.; van Wely, Madelon; Lambalk, Cornelis B.; Goddijn, Mariëtte; Custers, Inge M.; van Loendersloot, Laura L.; et al.
Abstract: Research question: How do infertility patients, endometriosis patients and health-care providers rate virtual care as an alternative to physical consultations during the first lockdown of the coronavirus disease 2019 (COVID-19) pandemic in the Netherlands, and how does this influence quality of life and quality of care? Design: Infertility patients and endometriosis patients from a university hospital and members of national patient organizations, as well as healthcare providers in infertility and endometriosis care, were asked to participate between May and October 2020. The distributed online questionnaires consisted of an appraisal of virtual care and an assessment of fertility-related quality of life (FertiQol) and patient-centredness of endometriosis care (ENDOCARE). Results: Questionnaires were returned by 330 infertility patients, 181 endometriosis patients and 101 healthcare providers. Of these, 75.9% of infertility patients, 64.8% of endometriosis patients and 80% of healthcare providers rated telephone consultations as a good alternative to physical consultations during the COVID-19-pandemic. Only 21.3%, 14.8% and 19.2% of the three groups rated telephone consultations as a good replacement for physical consultations in the future. A total of 76.6% and 35.9% of the infertility and endometriosis patients reported increased levels of stress during the pandemic. Infertility patients scored lower on the FertiQol, while the ENDOCARE results care seem comparable to the reference population. Conclusions: Virtual care seems to be a good alternative for infertility and endometriosis patients in circumstances where physical consultations are not possible. Self-reported stress is especially high in infertility patients during the COVID-19-pandemic. Healthcare providers should aim to improve their patients' ability to cope.